Prognostic role of maspin expression in patients with cervical dysplasia and cervical cancer. Issue 5 (20th February 2020) - Isci Bostanci, Esra; Guler, Ismail; Dikmen, Asiye U.; Erdem, Ozlem; Guner, Haldun; Onan, Mehmet Anil; Taskiran, Cagatay
Abstract: Aim: Mammary serine protease inhibitor (maspin) acts as a tumor suppressor through the inhibition of cancer cell invasion and metastasis. Paradoxically, maspin levels are increased in some types of malignant cells. The aim of this study was to investigate the maspin expression in cervical dysplasia and cervical cancer, and to analyze its' relation with survival. Methods: Maspin expression was detected by immunohistochemistry using labeled streptavidin biotin method to determine cytoplasmic and nuclear maspin expressions in cervical intraepithelial neoplasia grade 1 (CIN1), cervical intraepithelial neoplasia grade 2 (CIN2), cervical intraepithelial neoplasia grade 3 (CIN3) and cervical cancer. Results: A total of 89 patients with CIN (29 cases of CIN1, 30 cases of CIN2 and 30 cases of CIN3), and 27 patients with cervical cancer were included to the study. 7.8% of the patients with CIN had maspin staining positivity. On the other hand maspin staining was positive in 20 of 27 patients (74.1%) with cervical carcinoma ( P = 0.001). Of these patients 20 (100%) had cytoplasmic, and 8 (40%) had nuclear maspin staining positivity. Cytoplasmic maspin immunoreactive scores were found to be significantly higher in carcinoma group when compared to the patients with CIN1/3 (respectively; P = 0.01, P = 0.02). No difference was noted for nuclear maspin expression. Significant overall survival advantage was detected for patients with nuclear maspin staining ( P = 0.03). Conclusion: The current study shows that nuclear maspin expression is related with better overall survival in cervical cancer. Maspin staining can be a useful diagnostic marker to discriminate cervical intraepithelial neoplasia from cervical carcinoma.